Pendidikan Kesehatan Reproduksi Remaja Bagi Orang Tua Komunitas Pekerja Migran Asal Kampung Pandan, Malaysia: Adolescent Reproductive Health Education for Parents in the Migrant Worker Community from Kampung Pandan, Malaysia - Yuliani, Anita; Fatmawati, Ariani; Teesen, Gabriele Stefhany (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The "Adolescent Reproductive Health Education Program for Parents in the Migrant Worker Community of Kampung Pandan, Malaysia" aims to enhance parents' knowledge and involvement in guiding their adolescent children on reproductive health. The migrant worker community faces unique challenges in accessing health education, including the role of parents in educating their children about reproductive health. As faith-based and community-oriented organizations, PCIM and PCIA strive not only to educate but also to empower, particularly by providing relevant skills to improve quality of life. A total of 29 parents participated, with the majority aged 46-55 years and working as laborers or housewives. The results of pre-tests and post-tests showed an improvement in parents' understanding, with 59% demonstrating good comprehension of adolescent reproductive health and 66% showing a positive attitude toward educational activities. However, 24% of participants remained less engaged. Based on these findings, community-based counseling programs. have proven effective, although further approaches are needed to increase the involvement of all participants. Recommendations include targeted mentoring and collaboration with local health institutions.